The molecular basis of distinct aggregation pathways of islet amyloid polypeptide - Chan-Park, Mary B. (2012)
Abnormal aggregation of islet amyloid polypeptide (IAPP) into amyloid fibrils is a hallmark of type 2 diabetes. In this study, we investigated the initial oligomerization and subsequent addition of monomers to growing aggregates of human IAPP at the residue-specific level using NMR, atomic force microscopy, mass spectroscopy, and computational simulations. We found that in solution IAPPs rapidly associate into transient low-order oligomers such as dimers and trimers via interactions between histidine 18 and tyrosine 37. This initial event is proceeded by slow aggregation into higher-order spherical oligomers and elongated fibrils. In these two morphologically distinct types of aggregates IAPPs adopt structures with markedly different residual flexibility. Here we show that the anti-amyloidogenic compound resveratrol inhibits oligomerization and amyloid formation via binding to histidine 18, supporting the finding that this residue is crucial for on-pathway oligomer formation.